Evidence on market concentration in Malaysian dual banking system - Mohammed, Nafisah; Ismail, Abdul Ghafar; Muhammad, Junaina (Elsevier, 2015)
There are to two main purposes for this paper. Firstly, to analyse the link between concentration and competition in both Islamic and conventional banking market in Malaysia. Secondly, to analyse empirically the relationship of concentrations with several specific factors of the firms and other control variables. Structural approach is used to analyse the evolution in banking market concentration in both banking streams. The findings herein support the structure-conduct-performance (SCP) paradigm, where different concentration ratios show a decreasing trend over the study period, which reflect greater degree of competition in the Malaysian dual banking system.